2000
DOI: 10.1093/emboj/19.15.3857
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a repair enzyme of oxidatively damaged DNA, MutM (Fpg), from an extreme thermophile,Thermus thermophilusHB8

Abstract: The MutM [formamidopyrimidine DNA glycosylase (Fpg)] protein is a trifunctional DNA base excision repair enzyme that removes a wide range of oxidatively damaged bases (N-glycosylase activity) and cleaves both the 3¢-and 5¢-phosphodiester bonds of the resulting apurinic/apyrimidinic site (AP lyase activity). The crystal structure of MutM from an extreme thermophile, Thermus thermophilus HB8, was determined at 1.9 A Ê resolution with multiwavelength anomalous diffraction phasing using the intrinsic Zn 2+ ion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
164
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(169 citation statements)
references
References 65 publications
(104 reference statements)
5
164
0
Order By: Relevance
“…Although the protein construct used for this study comprises residues 2-342 (including the C-terminal hexa-His tag), there is no identifiable density beyond residue 290. A search with the DALI server (53) confirmed the expected structural similarity with other DNA glycosylases of the Fpg͞Nei family, Thermus thermophilus Fpg (TthFpg; PDB ID code 1EE8; C␣ rms deviation ϭ 2.4 Å, 29% sequence identity, Z score ϭ 21.0) (21) and EcoNei (PDB ID code 1K3W; C␣ rms deviation ϭ 3.1 Å, 25% sequence identity, Z score ϭ 17.7) (20). The numbers reported by DALI indicate that NEIL1 is structur- Rmerge ϭ ͚ ͉I Ϫ ͗I͉͘͞ ͚ I, where ͗I͘ is the average intensity from multiple observations of symmetry-related reflections.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Although the protein construct used for this study comprises residues 2-342 (including the C-terminal hexa-His tag), there is no identifiable density beyond residue 290. A search with the DALI server (53) confirmed the expected structural similarity with other DNA glycosylases of the Fpg͞Nei family, Thermus thermophilus Fpg (TthFpg; PDB ID code 1EE8; C␣ rms deviation ϭ 2.4 Å, 29% sequence identity, Z score ϭ 21.0) (21) and EcoNei (PDB ID code 1K3W; C␣ rms deviation ϭ 3.1 Å, 25% sequence identity, Z score ϭ 17.7) (20). The numbers reported by DALI indicate that NEIL1 is structur- Rmerge ϭ ͚ ͉I Ϫ ͗I͉͘͞ ͚ I, where ͗I͘ is the average intensity from multiple observations of symmetry-related reflections.…”
Section: Resultsmentioning
confidence: 83%
“…3). There are nonetheless significant differences: A segment comprising ␣H and the loop connecting ␣G and ␣H in NEIL1 corresponds to a region that has been shown to be disordered in the borohydride trapped covalent Nei-DNA (20) and Fpg-DNA (22, 24) complexes or complexes with DNA containing an abasic site (23,24), whereas it is ordered in uncomplexed TthFpg (21). The difference, however, is not just due to the presence or absence of DNA, but seems to also hinge on the presence of a nucleobase lesion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some members of these families have common npg substrates. OGG1, MutY, Nth and their homologs have HhH structure [42][43][44]; while MutM (Fpg) and Nei have H2TH motif [44][45][46][47].…”
Section: Oxidized Base-specific Dna Glycosylasesmentioning
confidence: 99%
“…Gao and Murphy [2] earlier reported that FPG-2 had a limited amount of activity in vitro on depurinated, UV-treated, and methylene-blue-treated DNA (but not on 8-oxo-G-containing oligonucleotides). FPG-2 contains the N-terminal domain and the H2TH motif in the C-terminal domain, but lacks the FPG-1 C-terminal sequence that corresponds to the bacterial zinc-finger motif [13]; this motif contributes to stabilization of the enzyme-DNA complex [14]. Other products of the Arabidopsis fpg gene splicing variants found from cloning and RT-PCR screens were not tested, but most of these are predicted to lack essential active site amino acids or have other major disruptions in their C-terminal amino acid sequences [1], so it seems unlikely that they would be active.…”
Section: Discussionmentioning
confidence: 99%